2015
DOI: 10.1016/j.cgh.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adults in the Hepatitis B Research Network in North America Reflect Their Country of Origin and Hepatitis B Virus Genotype

Abstract: Background & Aims Chronic hepatitis B virus (HBV) infection is an important cause of cirrhosis and hepatocellular carcinoma worldwide; populations that migrate to the US and Canada might be disproportionately affected. The Hepatitis B Research Network (HBRN) is a cooperative network of investigators from the United States and Canada, created to facilitate clinical, therapeutic, and translational research in adults and children with hepatitis B. We describe the structure of the network and baseline characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 12 publications
6
81
1
1
Order By: Relevance
“…Again, seropositivity rates were higher among foreign-born (1.6 %), in accordance with previous reports outlining seropositivity rates as high as 7.4 % in immigrants from highendemicity countries [21]. Data from the Hepatitis B Research Network (HBRN), including 1625 HBV seropositive adults from 21 clinical centers in North America, suggested that half of the HBV-infected population are men (median age 42 years) and 82 % were born outside of North America, with genotype B the most common (39 %) [22].…”
Section: Hbv Epidemiology In the Six Who Regions Americassupporting
confidence: 82%
“…Again, seropositivity rates were higher among foreign-born (1.6 %), in accordance with previous reports outlining seropositivity rates as high as 7.4 % in immigrants from highendemicity countries [21]. Data from the Hepatitis B Research Network (HBRN), including 1625 HBV seropositive adults from 21 clinical centers in North America, suggested that half of the HBV-infected population are men (median age 42 years) and 82 % were born outside of North America, with genotype B the most common (39 %) [22].…”
Section: Hbv Epidemiology In the Six Who Regions Americassupporting
confidence: 82%
“…Baseline characteristics of the HBRN immunology study participants (shown in Supplementary Table S2) resembled those reported in the entire HBRN cohort 25 with median age of 42 years, equal male/female distribution (55%:45%), Asian predominance (83%) and high prevalence of genotypes B (47%) and C (30%), followed by genotypes A (9%) and D (6%). The CHB phenotype groups displayed expected differences in liver function parameters, HBV DNA titers (e.g.…”
Section: Resultsmentioning
confidence: 67%
“…The Adult Cohort Study protocol has been described elsewhere 25 . In brief, the Adult Cohort Study enrolled hepatitis B surface antigen (HBsAg)-positive patients that were 18 years or older without evidence for hepatic decompensation, hepatocellular carcinoma, liver transplant or human immunodeficiency virus (HIV) infection, and not receiving antiviral therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The HBRN is a cooperative network of investigators from 21 geographically distinct clinical centers across the United States and one in Canada, a data coordinating center, virology testing laboratory and immunology center. The goal of the HBRN is to conduct clinical, scientific, epidemiological and therapeutic research in acute and chronic hepatitis B in both adult and pediatric patients who reside in North America (27). All protocols were approved by the Steering Committee and the Institutional Review Boards or Research Ethics Boards of the participating sites, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%